Combination of ionising radiation with hyperthermia increases the immunogenic potential of B16-F10 melanoma cells in vitro and in vivo. (2nd January 2016) - Werthmöller, Nina; Frey, Benjamin; Rückert, Michael; Lotter, Michael; Fietkau, Rainer; Gaipl, Udo S.
Abstract: Mild hyperthermia (HT) (41.5 °C for 30–60 min) has been shown in various cell culture systems, preclinical and clinical models to be a very potent radiosensitiser. Recent research suggests that local HT application in combination with standard tumour therapies such as radiotherapy (RT) and/or chemotherapy may not only improve local tumour control but also lead to systemic and immune mediated anti-tumour responses. Melanoma has been proven to be rather radioresistant and mostly only the addition of immunotherapy is capable of inducing beneficial anti-melanoma responses. This work therefore focuses on whether HT increases the immunogenic potential of B16-F10 mouse melanoma cells in combination with RT. The in vitro experiments revealed that combination of RT with HT resulted in an increased percentage of apoptotic and necrotic melanoma cells and an increased release of the danger signal heat shock protein 70 (Hsp70) and high mobility group box protein 1 (HMGB1). HT alone was also capable of inducing this release. We set up local irradiation and heating procedures of B16-F10 tumour-bearing C57/BL6 mice and revealed that the tumour growth of tumours treated with RT plus HT was significantly retarded compared to tumours treated only with RT. This combined treatment generated a beneficial tumour microenvironment by enhancing the infiltration of CD11c + /MHCII + /CD86+ dendritic cells, CD8+ T cells, and NK cells, and decreasing that of regulatory T cells and myeloid-derived suppressor cells. We conclude that HT in combination with RT has an immune-stimulating potential that might result in anti-tumour immunity.